Biotransformation: A Novel Approach of Modulating and Synthesizing Compounds - Roy, Proloy Sankar Dev; Singh, Brajeshwar; Sharma, Vikas; Thappa, Chandan (Journal for Research in Applied Sciences and Biotechnology, 2022)
Transformation of potential compounds into utilizable and beneficial forms is often cost involving and time consuming. Chemical transformation though was an existing opportunity catering our needs but due to environmental impacts and cost- benefit ratio analysis it proved futile and a new branch of transformation came into existence termed as biotransformation. Biotransformation is an excellent opportunity of tailoring compounds to cater our needs in a simple and is an eco-friendly approach. Biotransformation allows conversion of one component to another compound by application of biological systems. Fermentation based biotransformation of plant extract is a well-established world-wide standard technique used to maximize shelf-life, nutritional and organoleptic properties and to eliminate harmful substances from primary food substrates. Biotransformation by microbes has grown greatly from a small involvement in highly active fields of green chemistry, including the preparation of pharmaceutical drugs, in recent years. In addition fermentation processes have been targeted and optimized to enhance the production of active microbial metabolites using sufficient or suitable nutrients and with the correct microbial target for functional benefits. At present, significant attention has been given to biotransformation technology worldwide to develop medicines through the processing and enrichment of additional medicinally essential bioactive metabolites including terpenes, alkaloids, phenols, flavonoids and saponins. Biotransformation utilizing various biological systems can be used to modulate and in the enhancement of bioactive compounds in an environment promising way. Biotransformation is assumed to play a key role in green chemistry in future because of its sustainable approach. This review represents an overview of biotransformation techniques and its applications in a nutshell.